Estratigrafia e o uso de palinomorfos em um estudo da dinâmica sedimentar de formação da ilha Mutum, alto rio Paraná, Brasil. - Gonçalves, Ana Carolina (2014)
This paper deals with a stratigraphic study applied to samples from a core collected in Mutum Island, located in the Upper Paraná River, Paraná State, Brazil (22°45'31.98''S and 53°17'52.60''W). By using pollen and sediment analysis, one can identify a historical characteristic deposition of wetlands. In these areas there are several features in different stages of succession geomorphic flagged by water and geomorphological dynamics of the river, as well as their areas of sedimentary deposits. Thus, the analysis of the testimony four hydrological phases (channel, backwater, pond and marsh) whose characteristics show successive changes in lateral connectivity of the river and consequently of the palynomorphs occurrences recorded along the profile analysis were identified.